Фемінні мотиви в поезії Маріанни Кіяновської (на матеріалі збірки «Звичайна мова») - Шаф, О. (Літературознавчі обрії. Праці молодих учених, 2010)
The article deals with the poetic basis of the verse by Marianna Kiyanovska (in the book «The usual language»). The main motives «love as bodiness» and «motherhood as integrity» from the perspective of the authentic women’s experience representation, the peculiarities of it’s expression in the composition, stylistic, graphic techniques are studied.